2015
DOI: 10.1038/ncomms9492
|View full text |Cite
|
Sign up to set email alerts
|

A RIAM/lamellipodin–talin–integrin complex forms the tip of sticky fingers that guide cell migration

Abstract: The leading edge of migrating cells contains rapidly translocating activated integrins associated with growing actin filaments that form "sticky fingers" that sense extracellular matrix and guide cell migration. Here we utilized indirect bimolecular fluorescence complementation (BiFC) to visualize a molecular complex containing an MRL protein (RIAM or lamellipodin), talin, and activated integrins in living cells. This complex localizes at the tips of growing actin filaments in lamellipodial and filopodial prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 52 publications
6
114
0
1
Order By: Relevance
“…A similar result was also observed when a 5 b 1 integrin was used instead of integrin a IIb b 3 or the formation of Lpdtalin-integrin complexes (50). In this experimental approach, talin-bound Lpd, which is a RIAM paralog present in all species except C. elegans and Drosophila, also formed a complex with a 5 b 1 integrin at the tips of actin-based protrusions.…”
Section: Riam Is An Integral Part Of the Integrin Activation Machinerysupporting
confidence: 78%
See 2 more Smart Citations
“…A similar result was also observed when a 5 b 1 integrin was used instead of integrin a IIb b 3 or the formation of Lpdtalin-integrin complexes (50). In this experimental approach, talin-bound Lpd, which is a RIAM paralog present in all species except C. elegans and Drosophila, also formed a complex with a 5 b 1 integrin at the tips of actin-based protrusions.…”
Section: Riam Is An Integral Part Of the Integrin Activation Machinerysupporting
confidence: 78%
“…In contrast to RIAM, vinculin is enriched in maturing focal adhesions, which are present on and at the border of lamellipodia, where vinculin reinforces the ability of the adhesion to transmit and bear force (47,49). Live cell imaging combined with indirect bimolecular fluorescence complementation indicated that a RIAM-integrin a IIb b 3 -talin complex is enriched at the tips of growing actin filaments in lamellipodial and filopodial processes, thus revealing the molecular basis of the formation of the so-called sticky fingers of these protrusions (50). Although RIAM is most abundant at the cell edge and lamellipodium, it is subsequently reduced in mature adhesions due to direct competition with vinculin for binding to talin (48).…”
Section: Riam Is An Integral Part Of the Integrin Activation Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…RIAM is essential for inside-out activation of integrins in leukocytes (Klapproth et al, 2015), but surprisingly not in in platelets (Stritt et al, 2015). This suggests that there are alternative pathways, for example, acting through the RIAM paralogue lamellipodin (also known as RAPH1) (Lagarrigue et al, 2015).…”
Section: Recruitment Of Talin To Integrin Adhesion Sitesmentioning
confidence: 99%
“…In fibroblasts, both talins localise to FAs, and talin1 is recruited directly to the leading edge, via proteins like the Rap1 effector RIAM (Rap1‐interacting adapter molecule) 29, 30 and FAK (focal adhesion kinase) 31. In contrast, less is known about talin2 recruitment.…”
Section: The Talinsmentioning
confidence: 99%